Osteomyelitis and septic arthritis in neonatal lupus erythematosus patients - Virany Diana; Risa Etika; Martono Tri Utomo; Kartika Darma Handayani; Quri Meihaerani Savitri (Elsevier, 2022)
Osteomyelitis in neonates is quite uncommon and often appears without a typical sign. Clinicians' late diagnosis and inappropriate treatment may result in severe sequelae. We report a rare case of osteomyelitis and septic arthritis infant with a mother's previous medical history of systemic lupus erythematosus at nine years old. Anti Lupus Anticoagulant (LA) result shows the infant also suffers from neonatal lupus erythematosus (NLE). Early diagnosis and proper management of the patient may produce better outcomes.